Jacques Derrida and the humanities a critical reader (Cambridge Univ. Press, 2001)
This volume is a trans-disciplinary collection dedicated to Jacques Derrida's work. The assembled contributions constitute an investigation of the role of his work within the field of humanities, present and future.